The efficacy of 99mTc-HYNIC-PSMA SPECT/CT in detecting primary lesions and metastasis in newly diagnosed prostate cancer - Wang, Taisong; Zhao, Lingzhou; Qiao, Wenli; Sun, Na; Zhao, Jinhua; Xing, Yan (Frontiers in Oncology, 2023)
Purpose: Compared with PET/CT or PET/MRI, SPECT/CT is cheaper and more readily accessible. This study was designed to investigate the efficacy of 99mTc-HYNIC-PSMA SPECT/CT in detecting primary tumors and metastases in patients with newly diagnosed prostate cancer (PCa). Methods: A retrospective analysis of 31 patients with pathologically proven PCa was performed at Shanghai General Hospital from November 2020 to November 2021. Planar whole-body imaging was performed on all patients with a SPECT/CT scan of PSMA-positive regions 3-4 hours after intravenous injection of 740 MBq 99mTc-HYNIC-PSMA. Positive PSMA uptake lesions were evaluated, and SUVmean and SUVmax were measured in each lesion. Associations between SPECT/CT parameters and clinicopathologic factors (tPSA and Gleason Score) were analyzed. The diagnostic capability of SPECT/CT parameters, tPSA and GS in distant metastatic detection was evaluated by logistic regression. Results: The SUVmean and SUVmax of the high-risk stratification subgroups (tPSA>20 ng/mL, GS≥8, and tPSA>20 ng/mL and GS≥8) were higher than those of the low-moderate risk stratification subgroups, with sensitivities of 92% and 92%, respectively. Neither SPECT/CT parameters (SUVmean, SUVmax) nor clinicopathologic factors (tPSA, GS) had high sensitivity (80%, 90%, 80%, 90%, respectively, P<0.05) in distant metastatic prediction. For both the guideline tPSA level (20 ng/mL) and the cut-off level (84.3 ng/mL), the difference in the distant metastasis detection rate between the low predicted tPSA group and the high predicted tPSA group was statistically significant (0% vs. 47.62%, P=0.005; 9.09% vs. 88.89%, P=0.000, respectively). Twenty patients with pathological 99mTc-PSMA avid only in prostate beds underwent radical prostatectomy. Seven of them underwent lymph node dissection, a total of 35 lymph nodes were removed, and no lymph nodes were detected with metastasis, which was consistent with 99mTc-HYNIC-PSMA SPECT/CT. Conclusion: 99mTc-HYNIC-PSMA SPECT/CT is effective in the risk stratification and distant metastasis detection of primary PCa patients. It is of great value in guiding treatment strategies.